An EPIC journey to locate single‐copy nuclear markers in sea anemones. (19th August 2018) - Brugler, Mercer R.; González‐Muñoz, Ricardo E.; Tessler, Michael; Rodríguez, Estefanía
Abstract: Sea anemones (Order Actiniaria) are among the most diverse members of the subclass Hexacorallia and are an emerging model system. Unfortunately, defining species and creating robust phylogenies remain a serious challenge due to simple body plans that reduce the number of available morphological characters, slow mitochondrial sequence evolution and a complete absence of nuclear markers in the actiniarian molecular toolkit other than the ribosomal cistron. Defining species boundaries and phylogenetic relationships is imperative for advancing our understanding of sea anemone taxonomy and systematics. Herein, we utilized EPIC (exon‐priming intron‐crossing) primers, in addition to non‐standard PCR profiling conditions, to obtain sequence data for seven nuclear introns located within Calmodulin, Calpain, Nck Associated Protein 1 Homolog, Pescadillo Homolog, Signal Recognition Particle 54‐kDa Subunit, Transferase and Vacuolar ATP Synthase Subunit B. These new markers were employed to evaluate whether morphological variability in marginal tentacle protuberances is indicative of intraspecific variation or cryptic species in the shallow‐water anemone Phymanthus crucifer . Variability within these nuclear introns was compared to mitochondrial 12S, 16S and cox3, and nuclear 18S and 28S. PCR products of all nuclear introns were cloned to determine copy number and the resulting variability among clones was consistent with single‐copy markers. We also amplified and sequenced six of the seven introns in a sister species, Phymanthus loligo, to determine the degree of interspecific variation. In addition, we evaluate the applicability of a subset of these markers within Actinostola and conclude with a review of putative single‐copy markers used in octocoral and scleractinian phylogenetics.